Zaměření specifických prvků v areálu Admas - Koukal, Pavel (Vysoké učení technické v Brně. Fakulta stavební, 2017)
Diplomová práce se skládá ze dvou základních částí. První část práce je zaměřena na naskenování části areálu Admas pozemním laserovým skenerem. V této části je popsán úvod do laserového skenování, použité pomůcky a software, práce v terénu, postup od registrace mračna bodů přes zpracování mračna bodů až po jeho připojení do S-JTSK. Druhá část práce je zaměřená převážně na vyhotovení digitálního modelu reliéfu ze získaných dat. Dále se zabývá vyhotovením příčných řezů areálem dvěma způsoby – z digitálního modelu reliéfu a z naměřených dat získaných polární metodou. Výsledkem práce je zhodnocení dosažené přesnosti modelu reliéfu na základě porovnání s polární metodou.

The diploma thesis consists of two fundamental parts. The first part is focused on scanning a section of the Admas area by a terrestrial laser scanner. This section describes the introduction to laser scanning, necessary utilities and software, fieldwork, the process from the registration of a point cloud, through point cloud processing to its connection into the S-JTSK. The second part of the thesis is mostly focused on execution of the digital model of the relief from the acquired data. It also deals with the two methods of creating a cross-sectional drawing of the area - one is based on the digital model of the relief and the other on data obtained by the polar method. The outcome of the thesis is to assess the accuracy of the topographical model, based on the comparison with the polar method.
The surveing of specific elements in the area of Admas
Keywords: Pozemní laserové skenování; skener Faro Focus 3D; mračno bodů; Faro SCENE; Admas; Terrestrial laser scanner; scanner Faro Focus 3D; point cloud; Faro SCENE; Admas